Review Juridical The Crime of Sexual Violence Against a Child with Decisions (Studies Court ruling Surakarta State Number 92/pid.sus/2020/Pn Skt) - Muhammad Aldi Fathurrahman; Bambang Sukoco (Universitas Muhammadiyah Surakarta, 2023)
Children are part of the next generation of the nation's ideals in the future. currently crime against children is rife, one of which is sexual violence by deception of minors by adults. Theaproblem of this research is whether the regulation regarding criminal sexual violence according to criminal law and Islamic law and what is the basis for the judge's considerations in imposing a crime on a court decision Surakarta State Number 92/pid.sus/2020/Pn Skt. The method used is empirical normative. Collecting data with library studies (library research) and interviews (interview). The results of the research are included in the conclusion which shows that the defendant has violated the crime in Article 81 paragraph (2) of RI Law No. 17 of 2016 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2016 concerningathe Second Amendment to RI Law No. 23 of 2002 concerning Child Protection became Law Number 35 of 2014 Jo Article 64 paragraph (1) of the Criminal Code. The Panel of Judges sentenced the defendant to imprisonment for 6 (six) ayears, a fine. Based on the results that the authors obtained after conducting the research, the authorsapropose a suggestion that is, It is hoped that law enforcement officials will work together with the community in general and parents in particular should play an active role in efforts to prevent sexual violence against children.